Nutritional risk screening 2002 scale and subsequent risk of stroke-associated infection in ischemic stroke: The REMISE study - Chen, Xiaoli; Li, Dongze; Liu, Yi; Zhu, Ling; Jia, Yu; Gao, Yongli (Frontiers in Nutrition, 2022)
Background and aims: Malnutrition is confirmed to be closely related to poor prognosis in ischemic stroke patients. Stroke-associated infection (SAI) is a common and serious complication in stroke patients. The study aimed to explore the predictive value of the Nutritional Risk Screening Tool 2002 (NRS-2002) for SAI in ischemic stroke (IS) patients and the relationship between malnutrition and SAI. Methods: We enrolled patients with IS admitted to five major hospitals in Chengdu from January 2017 to February 2019. The NRS-2002 screening tool was used to assess nutritional status. Logistic regression analysis was used to explore the predictive value of NR2002 for SAI and the relationship between malnutrition and SAI. Results: A total of 594 IS patients were included in this study, among whom 215 (36.20%) patients were at risk of malnutrition, and 216 (36.36%) patients developed SAI. The AUC of the NRS-2002 was 0.644, and the NRS-2002 improved the predictive values of the A2DS2 for the SAI (P <0.001). Logistic regression analysis showed that patients with malnutrition had significantly higher risks of SAI (NRS-2002: OR=1.450, 95% CI: 1.184-1.692, P<0.001). Conclusion: The NRS-2002 score is a useful and simple tool for identifying the risk of SAI. Malnutrition is related to the development of SAI. Malnourished stroke patients may benefit from further nutritional supplements and management.